2017
DOI: 10.1038/ncomms15095
|View full text |Cite
|
Sign up to set email alerts
|

Spatial computation of intratumoral T cells correlates with survival of patients with pancreatic cancer

Abstract: The exact nature and dynamics of pancreatic ductal adenocarcinoma (PDAC) immune composition remains largely unknown. Desmoplasia is suggested to polarize PDAC immunity. Therefore, a comprehensive evaluation of the composition and distribution of desmoplastic elements and T-cell infiltration is necessary to delineate their roles. Here we develop a novel computational imaging technology for the simultaneous evaluation of eight distinct markers, allowing for spatial analysis of distinct populations within the sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
484
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 507 publications
(515 citation statements)
references
References 39 publications
28
484
3
Order By: Relevance
“…Random integration of sequential Abs within a multiplex panel may lead to imbalanced signals, incomplete staining through interference with previously applied tyramide signal amplification (TSA), disruption of epitopes, and removal of TSA fluorophores because of repetitive antigen-retrievals at high temperature 80,81 . Therefore, each Ab was tested individually for its optimal position in the sequence of multiplex staining to minimize interference with previous Ab-TSA complexes or by alteration of epitopes.…”
Section: Pathway Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Random integration of sequential Abs within a multiplex panel may lead to imbalanced signals, incomplete staining through interference with previously applied tyramide signal amplification (TSA), disruption of epitopes, and removal of TSA fluorophores because of repetitive antigen-retrievals at high temperature 80,81 . Therefore, each Ab was tested individually for its optimal position in the sequence of multiplex staining to minimize interference with previous Ab-TSA complexes or by alteration of epitopes.…”
Section: Pathway Analysismentioning
confidence: 99%
“…Multiplexed slides were scanned on a Vectra Multispectral Imaging System version 2 (Perkin Elmer) as described 80,81 . Briefly, a spectral library from spectral peaks emitted by each fluorophore from single stained slides was created with the inform Advanced Image Analysis software (InForm 2.4, PerkinElmer) and used for spectral unmixing of multispectral images allowing for identification of all markers of interest.…”
Section: Tissue Imaging Spectral Unmixing and Phenotypingmentioning
confidence: 99%
“…With this respect, it is of great importance to consider the spatiotemporal dynamics of different immune cell types that infiltrate into tumors . Spatial distribution of cytotoxic T cells in proximity to cancer cells has just recently been demonstrated to correlate with increased overall survival of patients with pancreatic cancer . Like the dynamics of immune reaction against tumors, infiltration of immune cells into tumors takes place .…”
Section: Immunological Basis For Design Of Multimodal Radio‐immunothementioning
confidence: 99%
“…130 Spatial distribution of cytotoxic T cells in proximity to cancer cells has just recently been demonstrated to correlate with increased overall survival of patients with pancreatic cancer. 131 Like the dynamics of immune reaction against tumors, 132 infiltration of immune cells into tumors takes place. 133 Hettich and colleagues demonstrated that irradiation with 2×12 Gy on consecutive days of B16 melanoma tumors induces a high infiltration of CD8+ T cells at day 5 after the last irradiation.…”
Section: Dynamics Of Immune Cell Infiltrationmentioning
confidence: 99%
“…Visualizing spatial phenomena in tumors has predominantly been limited to protein expression, cell type, or a single geostatistical measure. [11][12][13][14][15] While these measures have been shown to have modest clinical utility, they do not readily provide insight into underlying biological processes. We hypothesize that jointly monitoring six geostatistics will enable visualization of spatial processes at both the global and local scale.…”
Section: Introductionmentioning
confidence: 99%